ANALISIS KINERJA EKONOMI DAERAH KABUPATEN DAN KEBIJAKAN PENINGKATANNYA DI PROVINSI JAMBI - Yuvanda, Sesraria; Rachmad R, Muhammad; Abrar, Muhammad (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2025)
This study aims to identify regional economic performance by determining which regions demonstrate the best economic performance and to formulate policies for improving such performance. The research employs secondary data analysis covering nine regencies in Jambi Province over the period 2015–2024. The analytical model used is the Regional Economic Performance Index (REPI), which also serves as the basis for formulating policies to enhance regional economic performance. The results indicate that the average REPI of the nine regencies in Jambi Province is 73.37, categorized as good. Sarolangun Regency records the highest REPI at 78.39, while West Tanjung Jabung Regency has the lowest REPI at 71.29. Policy measures to improve the REPI include increasing the contribution of the industrial sector, optimizing the utilization of natural resources, controlling food distribution and production, expanding employment and business opportunities, improving the quality and skills of the labor force, and providing subsidies for basic necessities.